Umbilical Pilonidal Sinus - Al-Kadi, Azzam S. (International Journal of Health Sciences, 2014)
Abstract: Pilonidal sinuses are commonly encountered, but their occurrence in the umbilical area is rare. The author presents one such case of an umbilical pilonidal sinus in an obese male patient that presented with recurrent episodes of umbilical discharge. The condition was treated with sinus excision and umbilical reconstruction. There was no recurrence of the disease until one year of follow up. Key words: Umbilical pilonidal sinus, hair, granulation tissue, excision, recurrence